"Carl Laemmle Presents": A Story of Political and Cultural Risk in Germany, 1917–1934. Issue 3 (2021) - Fear, Jeffrey; Stanca-Mustea, Cristina
Abstract : Led by German-born Carl Laemmle, Universal Pictures devoted itself to winning over the German market in the interwar period. Yet the German market proved difficult to crack, owing to political risk and cultural distance. We argue that cultural differences kept most American films from becoming more successful, even those that were shown in German theaters and prior to the advent of sound film. Universal Pictures resorted to a film strategy of localization using German actors and directors, which proved a winning formula just as the Nazis came to power.